Future climate effects on lake volume of Sembrong Dam using MRI-AGCM3.2S - Farah Amirah Kamis, 1995-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2018